PENGEMBANGAN MODUL FISIKA BERBASIS CONCEPT MAPPING PADA MATERI ELASTISITAS DI SMA - Siti Dwi Rahayu; Trapsilo Prihandono; Agus Abdul Gani (JURNAL PEMBELAJARAN FISIKA, 2017)
Concept mapping was a way to find the concept relation which arranged systematically in the real illustration from the relationship of the core concept to the other concepts that was owned by a particular field of study. Therefore, this research was focused on the development of teaching materials in the form of module based on concept mapping in learning physics for Senior High School. The research produced a student book. This research aimed to determine the validity of book, student understanding level and student’s response after using module based on concept mapping, using 4-D development models. The result of this research indicated that the teaching material in the form of module based on concept mapping was valid with validity 4.2 from 5 categories. Meanwhile, students understanding level of module based concept mapping obtained an average value of 82.65% with category “understand”. Regarding the third purpose of the research, the students responded the module very positive for every aspect presented on the questionnaire. In short, module based concept mapping was good and appropriate alternative to be used as a learning material. Key words: module based on concept mapping, validity, student understanding level, response.